2021
DOI: 10.3171/2020.12.focus20846
|View full text |Cite
|
Sign up to set email alerts
|

International trends in grant and fellowship funding awarded to women in neurosurgery

Abstract: OBJECTIVEMetric tracking of grant funding over time for academic neurosurgeons sorted by gender informs the current climate of career development internationally for women in neurosurgery.METHODSMultivariate linear trend analysis of grant funding awarded to neurosurgeons in the NIH and World Research Portfolio Online Reporting Tools Expenditures and Results (RePORTER) was performed. Traveling fellowships for international neurosurgery residents sponsored by the AANS and Congress of Neurological Surgeons (CNS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…1,2 However, women are less likely than men to be awarded research grants. 3,4,5,6 Women grant recipients are likely to produce more publications and attain a higher research impact h-index than nonrecipients. 7 Blanchard et al 8 indicated that women early-career grant recipients gain economic, social and cultural capital, which are essential for promotion in a researcher career.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, women are less likely than men to be awarded research grants. 3,4,5,6 Women grant recipients are likely to produce more publications and attain a higher research impact h-index than nonrecipients. 7 Blanchard et al 8 indicated that women early-career grant recipients gain economic, social and cultural capital, which are essential for promotion in a researcher career.…”
Section: Introductionmentioning
confidence: 99%